Morality or competence? The importance of affirming the appropriate dimension of self‐integrity. Issue 4 (6th October 2016) - Jessop, Donna C.; Sparks, Paul; Jessop, Laura; Dodds, Lauren; Lynch, Sarah
Abstract : Objectives: Two studies explored the relative efficacy of a morality‐based versus a competence‐based self‐affirmation manipulation at increasing acceptance of personally relevant health risk information. In accordance with prior theorizing (e.g., Cohen & Sherman, 2014), it was hypothesized that the morality affirmation would be more effective than the competence affirmation in such contexts, as the former targets a different domain to that threatened by the health risk information. Design: Both studies employed a cross‐sectional experimental design. Methods: Participants were presented with a morality affirmation, competence affirmation, or no affirmation control prior to reading a message about the risks of (1) not engaging in daily dental flossing (Study 1) and (2) red meat consumption (Study 2). Participants subsequently completed a number of measures assessing acceptance of the message. Results: In line with predictions, findings from both studies demonstrated that the morality affirmation precipitated greater acceptance of personally relevant health risk information compared to the competence affirmation, as reflected in more positive attitudes (Studies 1 and 2) and intentions (Study 1). Study 2's findings further suggested that the superior efficacy of the morality affirmation in health‐related contexts could not simply be attributed to a general tendency for this affirmation to outperform the competence affirmation. Conclusions: The nature of the value affirmed may be a critical factor in determining the success of self‐affirmation manipulations in health‐related domains. Statement of contribution What is already known on this subject? Self‐affirmation has been shown to promote openness to personally relevant health risk information across a variety of behavioural domains. The most frequently utilized self‐affirmation manipulation involves participants reflecting on a personally important value; however, participants typically self‐select the value they reflect on. This means that the nature of the value that is affirmed may vary from person to person within a given study, seriously limiting the interpretability of the findings. What does this study add? This study manipulated the domain of the value affirmed prior to reading a health risk message. Findings suggest that a morality affirmation is most effective at promoting openness to the message. This study highlights the importance of value domain in determining the success of self‐affirmation.